(untitled) (Journal of Health, Population and Nutrition, 2010)
This study compared the costs of providing antenatal, delivery and postnatal care in the home and in a basic obstetric facility in rural Bangladesh. The average costs were estimated by interviewing midwives and from institutional records. The main determinants of cost in each setting were also assessed. The cost of basic obstetric care in the home and in a facility was very similar, although care in the home was cheaper. Deliveries in the home took more time but this was offset by the capital costs associated with facility-based care. As use-rates increase, deliveries in a facility will become cheaper. Antenatal and postnatal care was much cheaper to provide in the facility than in the home. Facility-based delivery care is likely to be a cheaper and more feasible method for the care provider as demand rises. In settings where skilled attendance rates are very low, home-based care will be cheaper. Key words: Comparative studies; Cost-benefit analysis; Healthcare costs; Maternal health; Obstetric care; Bangladesh DOI: 10.3329/jhpn.v28i3.5558 J HEALTH POPUL NUTR 2010 Jun;28(3):286-293